Pengaruh Frekuensi Perdagangan, Volume Perdagangan, & Kapitalisasi Pasar Terhadap Return Saham Pada Sektor Pariwisata Yang Terdaftar Di BEI - Maysie, Kristina (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2021)
Purpose, - This study aims to determine how much influence the trading frequency, trading volume, and market capitalization either partially or simultaneously on stock returns in the tourism sector listed on the IDX. Design/methodology/approach, - The approach used is a quantitative approach and uses secondary data. This study uses panel data analysis techniques (data pool) using Microsoft Excel, and Eviews 9. The population and sample in this study are all companies in the tourism sector that have been listed on the BEI, totaling 5 companies, and the sample in this study are 4 companies from the tourism sector that have been selected based on criteria using purposive sampling technique. Findings, - The results showed that: 1) Partially with the t-test stated that the trading frequency variable has a positive and significant effect on stock returns, trading volume and market capitalization variables have a negative and significant effect on stock returns; 2) Simultaneously with the F-test states that the independent variables (trading frequency, trading volume, and market capitalization) have a significant effect on the stock return variable